Screening of Mung bean Germplasm for Resistance against Cercospora Leaf Spot under Natural Field Conditions (Plant Bulletin, 2024)
Mung bean is an excellent protein source pulse crop grown throughout the world. Punjab province accounts for 80% area and production of mung bean in Pakistan. Mung bean is cultivated on a large scale for its green manuring ability and grain consumption. Mung bean is prone to economically important fungal, bacterial, and viral diseases. Cercospora leaf spot (CLS) caused by Cercospora canescens is one of the most serious disease concerns in Pakistan. The pulses program at the National Agriculture Research Centre, Islamabad is trying hard to get the resistant germplasm against CLS. Sixty-eight advance lines/approved varieties were evaluated in the augmented design under natural field conditions. Forty-one advance lines/approved varieties were found resistant and twenty-five advance lines/approved varieties were found moderately resistant. Two advanced lines/approved varieties did not perform well and were susceptible to CLS infection. This data indicates that the germplasm at pulses program is excellent in resistance against CLS under natural field conditions in the Arid Zone and can serve as potential future varieties.
Keywords: Mungbean; Cercospora leaf spot; Resistance germplasm; Pulses; Screening